Anion-Directed Assembly of a Bimetallic Pd/Ag Nanocluster: Synthesis, Characterization, and HER Activity - Yu-Rong Ni; Rugma Thekke Pangal; Michael N. Pillay; Tzu-Hao Chiu; Samia Kahlal; Jean-Yves Saillard; C. W. Liu (Molecules)
Palladium-doped silver nanoclusters (NCs) have been highlighted for their unique physicochemical properties and potential applications in catalysis, optics, and electronics. Anion-directed synthesis offers a powerful route to control the morphology and properties of these NCs. Herein, we report a novel Pd-doped Ag NC, [Pd(H)Ag13(S){S2P(OiPr)2}10] (PdHAg13S), synthesized through the inclusion of sulfide and hydride anions. This NC features a unique linear S-Pd-H axis enclosed in a 4-5-4 stacked arrangement of silver atoms. The distinctive hydride environment was characterized by NMR spectroscopy, and the total structure was determined by single-crystal X-ray diffraction (SCXRD) and supported by computational studies. Mass spectrometry and X-ray photoelectron spectroscopy (XPS) further confirmed the assigned composition. This unique construct exhibits promising hydrogen evolution reaction (HER) activity. Our findings highlight the potential of anion-directed synthesis for creating novel bimetallic NCs with tailored structures and catalytic properties.